How to make an apple pie and see the world - Priceman Marjorie (Dragonfly Books, 1994)
La 4e de couverture indique : "From the jungles of Sri Lanka to the apple orchards of Vermont, the energetic little baker searches far and wide to find the finest ingredients for her apple pie".
Keywords: Cuisine Anglais (langue) Ouvrages pour la jeunesse; Voyages autour du monde Anglais (langue) Ouvrages pour la jeunesse; Littérature américaine pour la jeunesse; Littérature anglaise pour la jeunesse; Livres illustrés pour enfants